SET THEORY APPLIED IN TECHNOLOGICAL PARADIGMS AND TRAJECTORIES - Garcia, Jose (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
The purpose of this study is to integrate set theory as a novel mathematical framework into the field of evolutionary and neo-Schumpeterian economics, to analyse the intricate web of influences on technological paradigms. By employing the language of set theory, we can delineate the technological paradigm and its various institutional and knowledge-based supportive forces as subsets of the Universal Set of the Paradigm. With the universal set of a paradigm and the subsets within it, the aim is to provide a framework to represent a paradigm and its nuances, as outlining the spectrum of interactions between subsets. Importantly, while this paper provides a structured approach to paradigm analysis, the adaptability of this tool also enables the creation of other scenarios, encouraging further application to different technological analyses. The aim is to offer a simple mathematical tool to enhance the theoretical and practical understanding of technological evolution, facilitating an analysis of different prisms of paradigm and trajectories concepts.